EXECUTIVE STOCK OPTION PLANS: UJI PENGELOLAAN LABA SELAMA VESTING PERIOD - Nur Fadjrih Asyik (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
This study examine earnings management behavior related to compensation in the form of stock options during implementation of the grant program (vesting period). The study also examine and identify the differences in behavior during the execution of stock options. Companies as a sample in this study is a company listed in the Indonesia Stock Exchange, which has adopted the Executive Stock Option Plan and restricted to the companies that publish financial statements as of December 31 for the year 2007 to 2009. Final sample of this research into as many as 21 sample companies and the number of observations are 63 observational studies. The result of testing H1 shows that the more stock options offered to employees, the managers more motivated to manage earnings down prior to offering stock options. The results are consistent with previous studies of the behavior of managers who expect the share price decline before the date of grant, so the manager to pay compensation for stock options with a relatively cheap price. The results of testing H2a and H2b show that the more stock options offered to employees, the managers more motivated to manage earnings upward after offering stock options. Results show that an early stage implementation of executive stock option plans, executives trend to behave increasing income until vesting period final